An Efficient Synthesis of Pyrrolidinone Derivatives in the Presence of 1,1′-Butylenebis(3-sulfo-3H-imidazol-1-ium) Chloride - Khaligh, Nader Ghaffari; Chong, Kim Foong; Mihankhah, Taraneh; Titinchi, Salam; Johan, Mohd Rafie; Juan, Joon Ching (CSIRO Publishing, 2018)
The catalytic efficiency of 1,1′-butylenebis(3-sulfo-3H-imidazol-1-ium) chloride as a sulfonic acid-functionalized ionic liquid was demonstrated for the synthesis of pyrrolidinone derivatives under mild conditions. The electronic effect of substituents on aniline derivatives was investigated. Further, a study on the structure-activity relationship of ionic liquids containing sulfonic groups for the synthesis of ethyl-2-(4-chlorophenyl)-4-hydroxy-5-oxo-1-(p-tolyl)-2,5-dihydro-1H-pyrrole-3-carboxylate was performed under optimal conditions. The results showed that the catalytic properties of ionic liquids containing two sulfonic or imidazole moieties with carbon spacers was superior to ionic liquids having one sulfonic or imidazole moiety with no carbon spacer.